2004
DOI: 10.1136/adc.2002.025577
|View full text |Cite
|
Sign up to set email alerts
|

Return to school after brain injury

Abstract: Aims: To examine return to school and classroom performance following traumatic brain injury (TBI). Methods: This cross-sectional study set in the community comprised a group of 67 school-age children with TBI (35 mild, 13 moderate, 19 severe) and 14 uninjured matched controls. Parents and children were interviewed and children assessed at a mean of 2 years post injury. Teachers reported on academic performance and educational needs. The main measures used were classroom performance, the Children's Memory Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 27 publications
3
99
0
3
Order By: Relevance
“…Prospective memory impairment is one of the most common sequelae of brain injury and can have a debilitating effect on the lives of young people with brain injury [1][2][3][4][5][6][7][8][9]. Research has suggested that using smartphones as compensatory aids can help to improve functioning in children and adolescents [1,18,20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective memory impairment is one of the most common sequelae of brain injury and can have a debilitating effect on the lives of young people with brain injury [1][2][3][4][5][6][7][8][9]. Research has suggested that using smartphones as compensatory aids can help to improve functioning in children and adolescents [1,18,20].…”
Section: Resultsmentioning
confidence: 99%
“…Memory impairment can interfere with learning and access to education, everyday adaptive functioning and social participation [5][6][7][8][9]. Thus, interventions targeted at improving prospective memory are often employed in cognitive rehabilitation, via remedial or compensatory strategies [10].…”
Section: Introductionmentioning
confidence: 99%
“…Enfin, les enregistrements et les documents écrits sont conservés sous clé puis seront détruits une fois que le délai de conservation légal exigé sera expiré. (Colantonio et al, 1998;Friedman et al, 1999;Hawley et al, 2004;Laloua, 2006;Light, McCleary, Asarnow, Satz, Zaucha et Lewis, 1998;Thompson et Irby, 2003). Que ce soit d'ordres neuropsychologique et psychique (Bourque, 2000;Hanks et al, 1999), cognitif (Khan et al, 2003;Shanmukhi et Panigrahi, 2003) Différents auteurs le rapportent, lorsqu'un TCC survient à cet âge, celui-ci aura de nombreux impacts sur la maîtrise des fonctions exécutives et le développement de l'identité, de l'estime de soi ainsi que de la confiance (Alvin, 2005;Bourque, 2000;Cimon et al, 2000;Laloua, 2006).…”
Section: Considérations éThiquesunclassified
“…Or il appert que peu d'études se sont intéressées spécifiquement à l'inclusion sociale des adolescents dans le contexte d'un TCC modéré (Colantonio et al, 1998;Hawley, Ward, Magnay et Mychalkiw, 2004;Khan et al, 2003). Bien que certaines études aient, par ailleurs, traité des adolescents souffrant d'un autre problème de santé, par exemple le cancer, l'asthme ou la fibrose kystique, celles-ci ne faisaient pas état de leur inclusion sociale, mais plutôt de leurs difficultés ainsi que de leurs besoins en matière de services et de soins de santé (Esmond, 2000;Hollis et Morgan, 2001;Ishibashi, 2001;Kari, Donovan, Li et Taylor, 1999;Whelan, 2003).…”
Section: Introductionunclassified
“…Slomine and Locascio (2009) recommended that interventions for cognitive deficits need to be integrated into children's classroom experience. However, Hawley et al (2004) pointed out that there is often a lack of communication between schools and caregivers regarding the extent of a TBI survivor's injury and his/her prognosis, which limits successful re-integration (Hawley et al, 2004). Caregivers and school personnel need to collaborate concerning the child's abilities and limitations, in order to develop an appropriate academic program.…”
Section: Cognitive Interventionsmentioning
confidence: 99%